Rancang Bangun Sistem Informasi Akademik dan Administrasi Digital berbasis Web di SD Aisyiyah Kota Malang - Denny Satria Kurniawan; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SD Aisyiyah Kota Malang is one of the private elementary schools under the auspices of the Aisyiyah organization that guides students in the academic process from grade one to grade six. Problems that often occur include lost academic information and in the redesign of lost academic information data needs to take from a little to several days. In addition to academic problems, there is also conventional learning so that the academic process is only effective if carried out in the school environment. This research aims to solve academic and administrative problems that are a requirement for students to get academic services, where the solution of this research is a web-based application that uses the Javascript programming language. This research uses the prototyping method to find out whether there are needs that are not in accordance with the wishes of users in the academic scope of SD Aisyiyah Kota Malang. Testing obtained the results of Basic Path Testing Unit in accordance with the design, valid functional testing and System Usability Scale testing which resulted in a score of 7.25 on the admin side and 9.25 on the teacher side. From the results of this test it is concluded that the application is quite helpful and easy and is quite well received by users.